Combined spectroscopy and electrical characterization of La:BaSnO3 thin films and heterostructures - Arnaud P. Nono Tchiomo; Emanuela Carleschi; Aletta R. E. Prinsloo; Wilfried Sigle; Peter A. van Aken; Jochen Mannhart; Prosper Ngabonziza; Bryan P. Doyle (AIP Advances, 2022)
For La-doped BaSnO3 thin films grown by pulsed laser deposition, we combine chemical surface characterization and electronic transport studies to probe the evolution of electronic states in the band structure for different La-doping contents. Systematic analyses of spectroscopic data based on fitting the core electron line shapes help to unravel the composition of the surface as well as the dynamics associated with increasing doping. These dynamics are observed with a more pronounced signature in the Sn 3d core level, which exhibits an increasing asymmetry to the high binding energy side of the peak with increasing electron density. The present results expand the current understanding of the interplay between the doping concentration, electronic band structure, and transport properties of epitaxial La:BaSnO3 films.